Peningkatan Kemampuan Servis Bawah Bola Voli Melalui Metode Pembelajaran Team Games Tournamen (TGT) - Rachmat Permadi; Sisworo Sisworo; Suratman Suratman (Universitas Negeri Semarang, 2024)
The purpose of this research is to find out whether the Teams Games Tournament (TGT) learning model influences volleyball learning outcomes in class X SMA Negeri 10 Semarang. This type of research is classroom action research (PTK) in the form of quantitative research. The subjects in this research were all students in class X-1 of SMA Negeri 10 Semarang, totaling 34 students, consisting of 11 male students and 23 female students. The results of data processing show that there were 3 students (9%) who completed the action before the action or pre-cycle, after being given the action in cycle I, there was an increase in the completion of learning outcomes to 16 students (47%). Then there was an increase in the completeness of learning outcomes in cycle II, namely as many as 28 students completed it or 82%. So, it is concluded that there is an influence of the Teams Games Tournament (TGT) learning model on volleyball learning outcomes in class X students at SMA Negeri 10 Semarang. Result of this Study, TGT can increase the students learning outcomes. TGT Methode should be implemented in other games like volleyball.